Differences in motivation during the bench press movement with progressive loads using EEG analysis - Maszczyk, Adam; Dobrakowski, Paweł; Żak, Marcin; Gozdowski, Paweł; Krawczyk, Magdalena; Małecki, Andrzej; Stastny, Petr; Zajac, Tomasz (Biology of Sport, 2019)
Considering our preliminary research with EEG analysis of the bench press in experienced powerlifters, we hypothesized that there would be significant differences in motivation between novice and elite powerlifters. Therefore the main objective of this study was to identify patterns of frontal alpha asymmetry (FAA) of the prime movers by alpha frequency band analysis (named as alpha motivation values) for each 35–100% one-repetition maximum (1RM) during the flat bench press. Ten novice powerlifters with no more than 2.5 years of resistance training experience and ten elite powerlifters with at least 7.5 years of training experience participated in the study. All participants were required to squat, bench press, and deadlift 100, 125, and 150% of their body mass, respectively. The athletes constituted a homogeneous group with respect to age (mean 22.3 ± 0.5 years). The EEG recordings were conducted using automatic headcups with 19 electrodes that were placed according to the International 10-20 Electrode Placement System. Signals from 8–12 Hz considering points F3 and F4 were analyzed. Furthermore, electromyographic (EMG) signals from the trapezius muscle were recorded. Before testing, moods and emotions of subjects were assessed to eliminate subjects with intense emotions. The results showed brain activity before, during and after cognitive and motor performance using electroencephalography (EEG). However, considering the still existing problems of movement artefacts during EEG measurements, eligible sports and exercises are limited to those that are relatively motionless during execution. Further studies are needed to confirm these preliminary results.